The Effectiveness of the Family Hope Programme on the Socio-Economic Welfare of Underprivileged Communities in Ballaparang Subdistrict, Makassar City - Patta Rapanna; Andi Sulfati; Rustan Rustan; Hernita Hernita (Doctoral Program of Social Science Pasundan University, 2025)
The type of research is qualitative using a phenomenological approach. The results of the research show that The Family Hope Programme (PKH) is a conditional social assistance programme that is effective in improving access to education and health care and alleviating the economic burden on underprivileged families. From a socio-economic perspective, PKH contributes significantly to reducing the risk of extreme poverty, improving basic welfare, and encouraging positive behavioural change in beneficiary families. However, its implementation still faces a number of weaknesses, such as the potential for dependence on assistance, inaccuracy in targeting recipients, limited assistance, and suboptimal long-term economic empowerment efforts. Therefore, PKH needs to be strengthened through improved data accuracy, more effective assistance, and integration with economic empowerment programmes so that the goals of self-reliance and sustainable poverty eradication can be achieved.